GAMBARAN KETANGGUHAN MENTAL ATLET GULAT PPLP RIAU - Lavelina Situmorang, Cristina Indri; Juita, Ardiah; Hidayat, Hirja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: the purpose of this study was to determine how the mental toughness of PPLP Riau wrestling athletes was described. The population in this study were PPLP Riau wrestling athletes, totaling 6 athletes. The data collection technique used in this research is to use an instrument in the form of a questionnaire which is distributed directly to the respondents. The analysis technique used is to pour the frequency in the form of a percentage. This study indicates that the description of the mental toughness of PPLP Riau wrestling athletes is in the Good category. With considerations based on the research and discussion that have been described, it can be concluded that the description of the mental toughness of PPLP Riau wrestling athletes is said to be good for men with a percentage of (63%). While for girls it is said to be good with a percentage of (58%).Key Words: Mental Toughness, Wrestling Athlete.